IMPLEMENTATION OF INTEGRITY ZONE DEVELOPMENT TOWARDS A CORRUPTION-FREE AREA AND A CLEAN SERVING BUREAUCRATIC AREA: STUDY AT BPS BULUNGAN REGENCY - Astutik, Elly (Erudio Journal of Educational Innovation, 2025)
Bureaucratic reform is one of the steps to organize a good, effective and efficient governance system, so that it is expected to be able to realize higher quality public services and increase the effectiveness of government management through the development of integrity zones. This study aims to present a description and analysis of the implementation of integrity zones, as well as inhibiting factors in the implementation of integrity zones at BPS Bulungan Regency. This study uses descriptive qualitative method. The results of the study show that BPS Bulungan Regency is committed to implementing integrity zones in six change areas, including change management, governance, structuring the HR management system, strengthening accountability, strengthening supervision and improving public services. However, until now it has not succeeded in obtaining the title of wbk/wbbm. Supporting factors consist of leadership commitment, quality human resources. The inhibiting factors consist of the lack of commitment of top leaders, human resources, socialization, monitoring and evaluation.